The Hidden Jewish Impulse In Saul Bellow Identity Groundbreaking His Novels The Dangling Man And (El-Wahat Journal for Research and Studies, 2025)
This Article Thoroughly Examines The Seminal Influence Exerted By Saul Bellow, One Of The Titans Of 20th-Century American Literature, On Jewish-American Literature In General And On His Novel The Dangling Man In Particular. This Deeply Introspective Writer's Works Are Replete With Rich Cultural Content That Has Indeed Influenced The Saga Of Jewish Bellow, Who Was Born To Russian Jewish Immigrants And Raised In Chicago. His Background Deeply Influences His Distinctive Point Of View; It Blends A Philosophical Depth With Realistic Detail. His First Novel, “The Dangling Man,” Foreshadows His Exploration Of Jewish Themes. An Existential Angst And A Search For Identity Are Characteristic Of The Experience Of Many In Today's Diaspora. The Article Explores How Bellow's Personal Life And Jewishness Shaped His Literary Style, Especially Regarding The Characterization And Construction Of Stories, Which Have Made An Indelible Mark On The Field Of Jewish-American Literature And The Larger American Literary Tradition.Keywords: Jewish Themes, Seminal Influence, Saga, Titans, Literature